A detailed research for determination of Bi/Ga partial substitution effect in Bi-2212 superconducting matrix on crucial characteristic features - Güner, Sait Barış; Zalaoğlu, Yusuf; Turğay, Tahsin; Özyurt, Ömer; Ülgen, Asaf Tolga; Doğruer, Musa; Yıldırım, Gürcan (JOURNAL OF ALLOYS AND COMPOUNDS, 2019)
This multidisciplinary study paves way to investigate the crucial of fundamental characteristic properties including the bulk density, electrical, superconducting, flux pinning mechanism, crystal structure quality and strength quality of interaction between the superconducting grains in the Bi(2.1)Sr(2.0)Ca(1.1)Cu(2.0)Oy (Bi-2212) superconducting materials with the partial replacement of gallium foreign impurity by bismuth nanoparticles in the crystal structure. Characterizations of polycrystalline ceramic materials prepared by standard ceramic route in the atmospheric air are performed by means of conventional experimental measurement methods such as powder X-ray diffraction, Archimedes water displacement, dc electrical resistivity versus temperature and critical current density examinations. All the bulk Bi-site Ga partial replaced materials exhibit the Bi-2212 superconducting phase within the different fraction levels (%73.1 -94.8), moderate self-field critical current densities 54-96 A/cm(2) and wide-ranging offset and onset critical transition temperature range of 45.65 K-84.52 K and 70.06 K-85.00 K. As for the experimental findings of bulk density and related degrees of granularity (porosity) parameters, the bulk density parameter is found to be between 5.76 g/cm(3) and 6.12 g/cm(3) when the corresponding residual porosity value is also obtained to be in a range of 8.57 % -2.86%. Moreover, the mobile hole carrier concentrations in the short-range-ordered antiferromagnetic Cu-O-2 layers are found to be in the range from 0.085 until 0.152. Additionally, the role of Ga/Bi partial substitution in the crystal lattice on the normal state resistivity, residual resistivity, residual resistivity ratio, vibrational mode intensities, texturing, superconducting volume fractions, mobile hole carrier concentrations, average crystallite sizes, Lotgering indices and cell parameters are discussed in details. All the experimental results and theoretical approaches show that the characteristic properties tend to improve regularly with the increment in the Ga foreign impurity level until x = 0.05 due to the increment in the crystal structure quality and interaction between the superconducting grains. After the critical Ga/Bi substitution level of x = 0.05, every feature degrades considerably. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Bi-2212 superconducting phase; Ga/Bi partial replacement; Crystal structure quality; Texturing; Porosity